2020
DOI: 10.1186/s12904-020-00601-5
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the 3 Wishes Project for compassionate end-of-life care: a qualitative evaluation of local adaptations

Abstract: Background: The 3 Wishes Project (3WP) is an end-of-life program that honors the dignity of dying patients by fostering meaningful connections among patients, families, and clinicians. Since 2013, it has become embedded in the culture of end-of-life care in over 20 ICUs across North America. The purpose of the current study is to describe the variation in implementation of 3WP across sites, in order to ascertain which factors facilitated multicenter implementation, which factors remain consistent across sites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
(37 reference statements)
0
11
0
2
Order By: Relevance
“…During this period, the research team liaised regularly with bedside staff to identify patients at high risk for dying, defined as a greater than 95% chance of death in the hospital or planned withdrawal of life support. At this institution, typical end-of-life care includes interventions designed to humanize the experience for patients and families as built into the daily workflow and staff training ( 16 ). To learn more about each patient, the clinical team telephoned family members, collating personal information about patients to share with staff via a whiteboard and in the electronic medical record (EMR) ( 12 ), which served to reassure families that the staff was interested in their loved one as a person ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…During this period, the research team liaised regularly with bedside staff to identify patients at high risk for dying, defined as a greater than 95% chance of death in the hospital or planned withdrawal of life support. At this institution, typical end-of-life care includes interventions designed to humanize the experience for patients and families as built into the daily workflow and staff training ( 16 ). To learn more about each patient, the clinical team telephoned family members, collating personal information about patients to share with staff via a whiteboard and in the electronic medical record (EMR) ( 12 ), which served to reassure families that the staff was interested in their loved one as a person ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the scaleup experience of the 3WP demonstrated that this can be possible. 28 A key learning of the scale-up experience of the 3WP, with relevance to our population, is the importance of local adaptation and a team approach to care. 28 Limitations Two main limitations of the methodology were identified.…”
Section: Discussionmentioning
confidence: 99%
“…28 A key learning of the scale-up experience of the 3WP, with relevance to our population, is the importance of local adaptation and a team approach to care. 28 Limitations Two main limitations of the methodology were identified. A single researcher coded the responses without benefit of validation by a second coder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3WP(3) began as a pilot project in a medical-surgical ICU in January 2013, and has been adopted and adapted in several North American centers. (4) Whether healthcare interventions are introduced through research or quality improvement initiatives, scaling up and sustaining them is challenging, even when worthwhile to patients, practitioners, or the public. (5) Program scale-up and sustainability are common terms in implementation science, with variable de nitions.…”
Section: Introductionmentioning
confidence: 99%